Paul Auster: Narrative and thought from a dual consciousness – The early fiction - Costa, Jaime (2020)
Ever since the publication of his first novel in 1985, Paul Auster has come to be considered one of America’s most influential novelists. He has also, without doubt, gained both recognition and notoriety of a larger audience by his incursions into film and, sporadically, into theater. Interestingly enough, Paul Auster’s success was first more evident in Europe where he was and, perhaps, still is, considered the ‘most French’ of American writers. This vision does not correspond to reality; Auster belongs to the sturdy trunk of American storytelling based on the American Renaissance, the American Romantic literature of Nathaniel Hawthorne, Herman Melville and Edgar Allan Poe. Indeed, much of present day French high culture is indebted to American thought, arts and letters. Paul Auster has been remarkably well received in Europe which has always provided a receptive ground for American letters; let us remember that Edgar Allan Poe’s success and, eventual rescue from oblivion, was due to French symbolism; that Emerson both prefigured and influenced cardinal twentieth century philosophers Martin Heidegger and Jacques Derrida and that, in general, Walt Whitman greatly influenced twentieth century European literature from Modernism to Postmodernism. In Paul Auster, the American letters have an example of the‘strong poet:’ an ironist who approaches philosophy in the same way that Richard Rorty’s philosophy salutes literature. Auster’s books open their pages to a whole plethora of subjects that have as much to do with literature as with a large variety of concerns related to human existence and endeavors: history, linguistics, theology, and, above all, as we have just mentioned, philosophy. Accordingly, Auster’s works are part essay and part fiction. The works analyzed in this book represent an effort on the part of Paul Auster as novelist and literary author in dealing with the complexity of the nature of writing. All of his narratives have heroes who are writers or, in some way or another, approximate the ideal of a writer. In these books there is a concern for what should be the value of inward reality and, likewise, for the value to be attributed to the external realities. It is in the coalescence of these two realms that Auster’s works come to life. It is the self, that ultimate instance, which provides sense — order — to the reality of the various voices — stories — that constitute the reality of experience. Again, one reality always leads to the other and, in their turn, they once again lead to the generation of other stories in a process that parallels that of the continuous semiosis of language. These narratives, stories, address themselves to the ultimate goal of generating genuine thought in an independent way to the specific fields of metaphysics, philosophy or science.